2016
DOI: 10.1007/s10549-015-3673-z
|View full text |Cite
|
Sign up to set email alerts
|

The TRAIL receptor agonist drozitumab targets basal B triple-negative breast cancer cells that express vimentin and Axl

Abstract: Purpose Previously, we found that GST-tagged tumor necrosis factor-related apoptosis inducing ligand (TRAIL) preferentially killed triple negative breast cancer (TNBC) cells with a mesenchymal phenotype by activating death receptor 5 (DR5). The purpose of this study was to explore the sensitivity of breast cancer cell lines to drozitumab, a clinically tested DR5 specific agonist; identify potential biomarkers of drozitumab-sensitive breast cancer cells; and determine if those biomarkers were present in tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…More reports have indicated remarkable diversity in the molecular characteristics of TNBC . Vimentin is identified as a mesenchymal marker for basal B TNBC, which makes epithelial cancer cells more aggressive with high motility and invasion . SUM1315MO2 and MDA‐MB‐231 belong to basal B TNBC with high expression levels of vimentin, which are highly sensitive to the c‐Src inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More reports have indicated remarkable diversity in the molecular characteristics of TNBC . Vimentin is identified as a mesenchymal marker for basal B TNBC, which makes epithelial cancer cells more aggressive with high motility and invasion . SUM1315MO2 and MDA‐MB‐231 belong to basal B TNBC with high expression levels of vimentin, which are highly sensitive to the c‐Src inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…24,[30][31][32] Vimentin is identified as a mesenchymal marker for basal B TNBC, which makes epithelial cancer cells more aggressive with high motility and invasion. 33,34 SUM1315MO2 and MDA-MB-231 belong to basal B TNBC with high expression levels of vimentin, which are highly sensitive to the c-Src inhibitor. By contrast, vimentin-negative TNBC cell lines HCC1937 and MDA-MB-468 have low adherent activity and cellular invasive ability (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…PARAs including drozitumab and dulanermin have been tested either alone or in combination with other agents in phase I and II clinical trials , with little clinical benefit observed to date which has led to the discontinuation of the development of PARAs in many cases . However, none of these clinical trials have examined the anticancer efficacy of PARAs against cancers in the bone such as OS.…”
Section: Discussionmentioning
confidence: 99%
“…Proapoptotic Receptor Agonists (PARAs), either as monotherapy or in combination with other agents, are generally well‐tolerated by patients with very few side effects and although phase 1/1b studies provided encouraging preliminary results, findings from randomized Phase 2 studies failed to demonstrate significant clinical benefit . Despite these clinical observations, there has been no investigation examining the anticancer efficacy of evofosfamide alone or in combination with either the Proapoptotic Receptor Agonists (PARAs) dulanermin (formerly known as Apo2L/TRAIL), or drozitumab for the treatment of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…T cells expressing a chimeric antigen receptor (CAR) of a TRAIL receptor single-chain antibody were capable of specific elimination of tumor cells with DR4. During interaction with tumor cells, the CAR-modified T cells were shown to trigger not only a DR4-induced apoptotic pathway, but also the mechanisms of T cell cytotoxicity [ 64 , 65 ].…”
Section: Antibodiesmentioning
confidence: 99%